Gema teologika: jurnal teologi kontekstual & filsafat keilahian (Fakultas Teologi, Universitas Kristen Duta Wacana, 2016)
"Gema Teologika is published by Faculty of Theology Duta Wacana Christian University periodically twice per year (April and October). The aim of the journal is to publish research articles in the fields of theology, especially contextual theology divinity studies, religious studies, and philosophy of religion in the contexts of Indonesia and Asia. Gema Teologika journal was first published in 1975 as Jurnal Gema Duta Wacana, and was changed as to Journal Gema Teologi in 2006-2015"